2023
DOI: 10.1007/s42994-023-00100-0
|View full text |Cite
|
Sign up to set email alerts
|

Shining in the dark: the big world of small peptides in plants

Abstract: Small peptides represent a subset of dark matter in plant proteomes. Through differential expression patterns and modes of action, small peptides act as important regulators of plant growth and development. Over the past 20 years, many small peptides have been identified due to technical advances in genome sequencing, bioinformatics, and chemical biology. In this article, we summarize the classification of plant small peptides and experimental strategies used to identify them as well as their potential use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 191 publications
0
10
0
Order By: Relevance
“…Specifically, transcript cleavage is facilitated by exoribonuclease activity, while translation inhibition happens through targeting the 5 untranslated region to prevent ribosome recruitment [40]. Notably, a type of peptide known as miRNA-encoded peptides (miPEPs) is translated from short open reading frames (sORFs) in the 5 leader sequence of pri-miRNAs [41,42]. These peptides promote the transcription of their corresponding pri-miRNAs, thus regulating many biological processes [43].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Specifically, transcript cleavage is facilitated by exoribonuclease activity, while translation inhibition happens through targeting the 5 untranslated region to prevent ribosome recruitment [40]. Notably, a type of peptide known as miRNA-encoded peptides (miPEPs) is translated from short open reading frames (sORFs) in the 5 leader sequence of pri-miRNAs [41,42]. These peptides promote the transcription of their corresponding pri-miRNAs, thus regulating many biological processes [43].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Major bottlenecks regarding the synthesis of peptides, even in smaller concentration, is quite expensive and difficult to adopt for agricultural produce (Feng et al, 2023). Majority of small signaling peptides undergo C-terminal processing occurs to produce mature signals (Mastubayashinet al, 2011, Mastubayashinet al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which plant lncRNAs function are numerous, and some of them are better understood in animals [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Recent studies have shown that the short open reading frames (sORFs) of some plant lncRNAs encode functional small peptides (micropeptides) with a size of around 5 to 100 amino acids [ 10 , 12 , 17 , 18 , 19 , 20 , 21 , 22 ]. Importantly, these lncRNAs also include precursors of many microRNAs, which code for peptides called miPEPs (peptides encoded by primary microRNAs), and some trans-acting siRNAs [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the short open reading frames (sORFs) of some plant lncRNAs encode functional small peptides (micropeptides) with a size of around 5 to 100 amino acids [ 10 , 12 , 17 , 18 , 19 , 20 , 21 , 22 ]. Importantly, these lncRNAs also include precursors of many microRNAs, which code for peptides called miPEPs (peptides encoded by primary microRNAs), and some trans-acting siRNAs [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Currently, bioinformatic tools as well as experimental methods such as mass spectrometry, ribosome mapping and in vitro translation are used to reveal the potential translational products of lncRNAs [ 10 , 16 , 17 , 19 , 21 , 24 , 32 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%